2022
DOI: 10.1038/s41533-022-00318-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical recommendations for dry powder inhaler use in the management of COPD in primary care

Abstract: Over 1400 patients using dry powder inhalers (DPIs) to deliver COPD maintenance therapies were recruited across Europe and Australia. Their peak inspiratory flow (PIF) was measured, inhaler technique was observed, and adherence to treatment assessed. From relating the findings with patient health status, and thereby identifying critical errors, key clinical recommendations for primary care clinicians were determined, namely – measure PIF before prescribing a DPI to ensure inhalation manoeuvre ability is well-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The prevalence of suboptimal peak inspiratory flow rates in hospitalized patients with COPD is shown to vary according to the internal resistance of DPI inhalers [ 25 ]. As studies of DPI use have shown that suboptimal peak inspiratory flow is associated with poorer health status, increased hospitalization and healthcare resource utilization, [ 26 , 27 ] as well as lower treatment adherence [ 28 ], it is important to assess whether sufficient peak inspiratory flow is consistently achieved by patients to ensure they are matched with an appropriate inhaler [ 26 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of suboptimal peak inspiratory flow rates in hospitalized patients with COPD is shown to vary according to the internal resistance of DPI inhalers [ 25 ]. As studies of DPI use have shown that suboptimal peak inspiratory flow is associated with poorer health status, increased hospitalization and healthcare resource utilization, [ 26 , 27 ] as well as lower treatment adherence [ 28 ], it is important to assess whether sufficient peak inspiratory flow is consistently achieved by patients to ensure they are matched with an appropriate inhaler [ 26 28 ].…”
Section: Discussionmentioning
confidence: 99%
“… 37 , 38 However, current smokers with COPD may have a heightened awareness and concern regarding the potential cognitive effects of COPD, as smoking is a well-established risk factor for the development and progression of the disease. 49 The influence of smoking cessation interventions and counseling in healthcare settings may also contribute to increased discussions about cognitive symptoms among current smokers with COPD, 50 highlighting the importance of targeted support for smokers with COPD. Patient-centered communication is crucial to ensuring that patients with chronic respiratory conditions understand their diagnoses and feel supported in self-managing their cognitive health.…”
Section: Discussionmentioning
confidence: 99%
“…This evaluation should include the ability of the patient to perform the required inhalation technique: “slow and steady” for pMDIs and SMIs, forcefully or hard and fast for DPIs, and normal tidal breathing for nebulizers ( Figure 1 ). Other considerations include the continuity of the inhaled delivery system, if possible, as provided by health insurance or an approved formulary as well as the patient’s cognitive function, manual function/dexterity, and PIFr ( Figure 1 ) ( 37 , 56 ). It is important that HCPs prescribe inhaled delivery systems they are familiar with, know how to use, and are able to demonstrate and teach correct technique to patients.…”
Section: Discussionmentioning
confidence: 99%